PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN UKURAN DEWAN PENGAWAS SYARIAH TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (Studi Empiris Pada Bank Umum Syariah di Indonesia Tahun 2010-2014) - Ramadhani, Febry; ', Desmiyawati; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examines the influence firm size, profitability, leverage and sharia supervisory board size to the Islamic Social Reporting disclosure. The population of this research are all of Islamic Banks in Indonesia in 2010-2014. The method of determining the sample is by using purposive sampling method and obtained 45 observations. The data processing method used in this study is the multiple regression analysis with the help of a computer program SPSS version 17.0. The result of this study indicates: (1) firm size has a significant influence toward the Islamic Social Reporting disclosure with significance value 0,000, (2) leverage has a significant influence toward the the Islamic Social Reporting disclosure with significance value 0,002, (3) sharia supervisory board size has a significant influence toward the Islamic Social Reporting disclosure with significance value 0,006, (4) but profitability does not have a significant influence toward the Islamic Social Reporting disclosure. The magnitude of the effect (R2) of firm size, profitability, leverage and sharia supervisory board size to the Islamic Social Reporting disclosure is 67,8% while the remaining 32,2% is influenced by other independent variabels that are not observeved in this study.Keyword: Islamic social reporting disclosure, firm size, profitability, leverage, and sharia supervisory board size.